2019
DOI: 10.1016/j.ghir.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel alternatively-spliced 5′ exon in the human insulin-like growth factor I (IGF-I) gene, expressed in liver and some cancers

Abstract: Article (Accepted Version) http://sro.sussex.ac.uk Wallis, Michael (2019) Characterization of a novel alternatively-spliced 5' exon in the human insulin-like growth factor I (IGF-I) gene, expressed in liver and some cancers. Growth Hormone and IGF Research, 46-47. pp. 36-43.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Pituitary transcriptomes for various mammals, birds, amphibia and fish were accessed through the NCBI SRA database, and used to assess transcription levels of POU1F1 , and details of splicing patterns. Expression profiles were established as described previously [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pituitary transcriptomes for various mammals, birds, amphibia and fish were accessed through the NCBI SRA database, and used to assess transcription levels of POU1F1 , and details of splicing patterns. Expression profiles were established as described previously [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was recently reported that an additional exon is present in the humans (mainly in the liver), located upstream from exon 1. This fragment can be spliced directly into exon 3, or, less often, into exon 1 [ 54 ].…”
Section: Igf1 Gene Structure and Signalingmentioning
confidence: 99%
“…Finally, as result of alternate promoter usage and differential splicing of IGF1 , at least six variants (isoforms) of mature mRNAs, i.e., IA, IB, IC, IIA, IIB, and IIC are generated in humans. All transcripts contain exons 3 and 4, encoding the mature 70-kDa IGF1 protein, while exons 5 and 6, which are alternatively spliced, code for the three C-terminal E peptides: Ea (exon 6), Eb (exon 5) and Ec (fragments of exons 5 and 6) [ 4 , 21 , 23 , 54 , 78 ] ( Figure 1 ).…”
Section: Igf1 Gene Structure and Signalingmentioning
confidence: 99%
See 2 more Smart Citations